2019
DOI: 10.20472/es.2019.8.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wealth Diversity (Case of Lithuania)

Abstract: The high level of income and wealth distribution in the world is recognized as a phenomenon that leads to negative economic and social consequences. The imperfection of redistribution levers in the economy has created conditions for the concentration of resources, material goods and wealth in small population groups. Today, the economic system is not focused on majority of the population, and therefore the high level of inequality and its consequences for economic growth, well-being and human development canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Moreover, Lithuania is still suffering high socio-economic inequality [ 19 ]. The study on Life Quality, conducted in Lithuania in 2014, demonstrated strong associations between the net income per month and overall satisfaction with life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lithuania is still suffering high socio-economic inequality [ 19 ]. The study on Life Quality, conducted in Lithuania in 2014, demonstrated strong associations between the net income per month and overall satisfaction with life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first calculations of global inequality were made in the early 1970s (Berry, Bourguignon, & Morrison, 1983). Trends in global inequality and the causes of change have been studied by Atkinson (1998), Ravallion (2001), Bresler (2000), Lee and Son (2016), and Rakauskienė et al (2017), etc.…”
Section: The Concept Of Inequality and The Factors Influencing Itmentioning
confidence: 99%
“…Meanwhile, Rakauskienė et al (2017) divide the factors determining economic inequality into three broad groups: economic, socio-demographic and psychological factors. The authors state that some factors affect inequality directly, othersindirectly, and others form the medium, circumstances for the mentioned factors.…”
Section: The Concept Of Inequality and The Factors Influencing Itmentioning
confidence: 99%
See 1 more Smart Citation
“…A huge volume of literature documents that household energy and energy and housing poverty is increasingly vital for maintaining good health and is reflected in policymakers' decisions. Many authors deal with the issue of poor housing [20][21][22], energy poverty [23][24][25][26], socioeconomic disadvantage [27][28][29] and climate change [30][31][32] from various perspectives. Pala [33] considers climate change as one of the crucial factors of household's well-being, Stanimir [34] discusses socioeconomic disadvantages connected to poverty through the lens participation of vulnerable communities in labor market and their preference of immediate remuneration in exchange of longer-term stability and career growth.…”
Section: Literature Reviewmentioning
confidence: 99%